The level of reflective thinking Skills by the teachers of the first cycle of basic education and its relationship with Self-efficacy (Damascus University Journal of educational and Psychologyical sciences, 2021)
The Current Study aimed to identify the level of reflective thinking skills by the teachers of the first cycle of basic education and its relationship with self-efficacy in the light of some variables ( gender, educational qualification, experience in teaching) for the teacher.The study sample consisted of (250) teachers who have to answer two scales questions , the reflective thinking skills scale, and the self-efficacy scale.The study found that the level of reflective thinking skills was low with an average account (8.67), and every skill of skills, and the level of self-efficacy was high, with a mean (3.97), and that teachers were more effective in the classroom management after a mean (4.07), and the least in education strategies after a mean (3.85). The results also showed that there were statistically significant differences between the average score differences of  research sample of reflective thinking skills return to educational qualification for the benefit of graduate students ,  and the existence of differences depending on the variable of experience for the benefit of people with the most experience. Also, the results indicated that there was a positive correlation between the average scores of teachers on a the reflective thinking skills scale and  their grades on the self-efficacy scale, as it can predict the skills of reflective thinking through self-efficacy.In light of the previous findings the study offered a series of suggestions on how to rais the level of reflective thinking skills, and raise the level of self-efficacy.
Keywords: : self-efficacy; Reflective teaching skills; teachers